2001
DOI: 10.1038/sj.bjp.0703863
|View full text |Cite
|
Sign up to set email alerts
|

The sulphonylurea glibenclamide inhibits multidrug resistance protein (MRP1) activity in human lung cancer cells

Abstract: 1 Glibenclamide, a sulphonylurea widely used for the treatment of non-insulin-dependent diabetes mellitus, has been shown to inhibit the activities of various ATP-binding cassette (ABC) transporters. In the present study, its e ects towards multidrug resistance protein 1 (MRP1), an ABC e ux pump conferring multidrug resistance and handling organic anions, were investigated. 2 Intracellular accumulation of calcein, an anionic dye substrate for MRP1, was strongly increased by glibenclamide in a dose-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 44 publications
2
58
0
Order By: Relevance
“…Furthermore, intracellular accumulation of vincristine, another MRP1 substrate, was shown, and this indicates that glibenclamide might act as a sensitizer of cancer cells to chemotherapeutic agents. Even though the MRP1-inhibiting dosage of the sulfonylurea might preclude its clinical application, these results confirm its role as a general ABC transporter inhibitor [24].…”
Section: Glibenclamidesupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, intracellular accumulation of vincristine, another MRP1 substrate, was shown, and this indicates that glibenclamide might act as a sensitizer of cancer cells to chemotherapeutic agents. Even though the MRP1-inhibiting dosage of the sulfonylurea might preclude its clinical application, these results confirm its role as a general ABC transporter inhibitor [24].…”
Section: Glibenclamidesupporting
confidence: 65%
“…Glibenclamide seems to directly bind and block MRP at higher concentrations than those permitted in affected patients without toxicity [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated the existence of an additional, energized ABA-GE transport mechanism. The addition of the known ABC transporter inhibitor orthovanadate (1 mM) or glibenclamide (0.1 mM; Martinoia et al, 1993;Payen et al, 2001) likewise reduced the ABA-GE uptake activity, by 26% or 51%, respectively. Combining the inhibitors of ABC transporters and V-ATPases, orthovanadate and bafilomycin A1, resulted in 50% reduction of the ABA-GE uptake activity.…”
Section: Enzymatic Synthesis Of Radiolabeled Aba-gementioning
confidence: 99%
“…In addition, MRP1 can even shift drugs out of cells into the extracellular fluid by vesicle transportation or exocytosis (14,18,19). Numerous studies have shown that inhibition of MRP1 expression by a variety of methods eased the development of drug resistance, thus supported clinical chemotherapy (20)(21)(22). Regarding the expression of MRP1 in esophageal cancer, it has been demonstrated that MRP1 often overexpressed in different esophageal cancer cell lines or cancer tissues of patients (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%